Structural, Optical, and Morphological Evaluation of Ag-Doped ZnO/CuO/Porous Silicon Heterojunctions for Optoelectronic Applications: Evaluasi Struktur, Optik, dan Morfologi Heterojunctions ZnO/CuO/Silikon Porous yang Doping Ag untuk Aplikasi Optoelektronik - Jenan Saddam; Muneer Jaduaa (Universitas Muhammadiyah Sidoarjo, 2026)
General Background Renewable energy technologies increasingly rely on advanced heterojunction architectures to improve light harvesting and charge transport in optoelectronic devices. Specific Background Multilayer systems combining ZnO, CuO, and porous silicon offer complementary electronic and optical properties, while plasmonic silver incorporation provides additional light–matter interaction pathways. Knowledge Gap However, a systematic experimental correlation between Ag doping concentration, nanostructural evolution, optical behavior, and photovoltaic response in ZnO/CuO/PSi heterojunctions remains insufficiently explored. Aims This study aims to fabricate and evaluate Ag-doped ZnO/CuO/porous silicon heterojunction devices and to examine the role of silver concentration on structural, optical, and electrical characteristics. Results Structural and morphological analyses reveal refined crystallite sizes and pronounced morphology evolution with increasing Ag content, accompanied by enhanced visible-light absorption and bandgap reduction to 2.78 eV at 7% Ag doping. Photovoltaic measurements demonstrate a maximum open-circuit voltage of 3300 mV, a fill factor of 45.09%, and a power conversion efficiency of 0.3125% for the optimized device. Novelty The work provides an integrated experimental assessment linking plasmonic Ag doping to interface engineering and device-level performance within a single heterojunction framework. Implications These findings offer practical guidance for designing cost-effective optoelectronic devices and advancing plasmonic-assisted multilayer solar cell architectures. Keywords: Ag-doped ZnO, CuO Heterojunction, Porous Silicon, Plasmonic Nanoparticles, Photovoltaic Devices Key Findings Highlights: Progressive silver incorporation induces significant morphological and crystallographic modification in multilayer structures. Visible-light absorption increases markedly due to combined plasmonic and bandgap engineering mechanisms. Optimized heterojunction configuration exhibits superior voltage output and charge collection behavior.